Acta neuropathologica communications (BioMed Central, 2013)
"Acta Neuropathologica Communications publishes experimental and descriptive articles on the pathology of nervous system and skeletal muscle disorders and on mechanisms of neurological disease using morphological, molecular and cell biology methods."